Two Years into the Crisis: Signs of Severe Coping Strategies that are Impacting on Children - Mendoza, Ronald U (Archīum Ateneo, 2010)
It has been two years since the first international food price spike affected countries’ access to world food markets. Since the onset in early-to-mid 2008, international food prices have relaxed but remain well above their long-run averages. In many countries, national food prices have remained sticky, and in some have actually continued to ascend in 2009 (World Bank, 2010). The global economic slowdown has compounded high food prices by eroding income and purchasing power in many parts of the world. UNICEF’s efforts to track child and maternal nutrition have raised alarms for many countries that had already indicated serious challenges even before the brunt of the food price volatility and global economic slowdown (UNICEF, 2009). This working brief draws on ongoing work by UNICEF and its partners, and it surveys recent emerging evidence relating to how households are coping with the aggregate shocks in 2008 and 2009. The main finding is stark: field reports and surveys by think tanks, the UN and other development agencies confirm the rising risk faced by children, women and poor families in a number of developing countries.